The ICT enhancing the creativity through collective intelligence - Jaime Meza; Oswaldo Ortiz; Sonia Roman; Josep M. Monguet; Martha Tomala (European Alliance for Innovation (EAI), 2017)
Nowadays, society and organizations face an accelerated innovation that requires of professionals with new skills and attitudes, especially those related to collective creativity. However, educational environments are slowly integrating emerging paradigms limiting the contribution to the development of key skills related to innovation. Multiple investigations claim that teachers have conservative attitudes toward collaborative schemes, while employers generally recognize the effectiveness of creativity at work. Management of ideas is the core of creativity in innovation processes in the industry and in production and service management. This depends largely on the collective work and individual social skills, as well as on the capabilities that information technology and communication (ICT) provide. This article presents a process of collective ideas refinement (CIR) and combines paradigms of swarm creativity and social skills as a means to capture the participants' emotions.